The Performative Machine: Transfer of Ownership in a Northwest Russian Reindeer Herder Community (Kola Peninsula) - Konstantinov , Yulian; Vladimirova, Vladislava (2006)
The article is based on longitudinal fieldwork with reindeer herders in the Kola Peninsula, northwest Russia. Its main ethnographic focus is SKhPK Tundra of Lovozero. The main argument is that a state of communal affairs under the dominance of the state farm (sovkohz) , during the Soviet period, privileged domestic economies of the farm workers to be supported by the collective assets of the farm. The authors see this state of "the private-in-the-collective" arrangement as "sovkhoism" and view the present variety of rural organizational forms in Russia as greater or lesser departures from it.